Venous stenting: Long‑Term Patency, Outcome Predictors, and Evolving Practice in Post‑Thrombotic Syndrome - Dang , Khoa Dang (Journal of Posthumanism, 2025)
Background: Iliofemoral venous stenting has become an essential treatment for chronic post-thrombotic syndrome (PTS) and iliofemoral venous obstruction. It can provide permanent relief of symptoms that cannot be corrected by other means through the outflow blockage. Objectives: The aim is to summarise the current primary clinical data on venous stenting for PTS, critically analyse trends in long-term patency, identify predictors of outcomes that are consistently observed, and identify new therapeutic approaches that would allow fine-tuning patient selection and maximising stent performance. Methods: Ten primary studies have been summarised in this review. The studies consider long-term patency, the features of anatomy and clinical appearance predictive of success, the patient-reported outcomes, and the performance of dedicated venous stents. Results: The findings indicate high technical success and significant improvements in pain, swelling, function, and quality of life in both acute and chronic patients. The rates of patency vary, though: lesions in non-thrombotic iliac veins are more likely to support patency, whereas PTS is associated with lower patency due to issues with inflows, scar tissue formation, and increased stent sets. In the literature, total elimination of clots, good inflow quality, and accurate stent placement were the strongest predictors of good results. Conclusions: The new-generation stents, such as Venovo and V-Mixtent, are performing well in terms of safety and efficacy, but results remain sparse in patients with severe fibrosis. Although studies vary in design and follow-up criteria, the overall evidence supports venous stenting as an effective and evolving treatment. Stricter comparative trials are needed to improve device selection, establish standard imaging criteria, and improve long-term outcomes